The relationship between trait emotional intelligence and problematic alcohol use among college students - Robert E Davis; Nicole A Doyle; Krishen D Samuel; Amanda H Wilkerson; Vinayak K Nahar (Tabriz University of Medical Sciences, 2022)
Background: Problematic alcohol use among college students is a significant public health concern. Emotional intelligence (EI), or the ability to detect one's own and others' emotions and to use this information to direct behavior, is suggested to mitigate problematic alcohol use. The purpose of this study was to examine the relationship between EI and problematic alcohol use among college students while controlling for drug use covariates. Methods: This cross-sectional study utilized an online survey comprised of previously validated measures to determine EI, problematic alcohol use, and drug use among college students from a large, public university in the south-central United States. Regression modeling and independent samples t-test were used to determine the relationship between EI and problematic alcohol use. Results: Problematic alcohol consumption was reported among 27.3% of participants (n=587). In regression modeling, EI demonstrated a significant, protective effect on problematic alcohol use (b=-0.050, P<0.001, 95% CI: -0.076 - -0.023), when adjusting for important covariates. Independent samples t-test showed that students who screened positive for harmful alcohol use reported significantly lower EI values than those who did not (Mean difference=4.53, t=2.98, P=0.003, 95% CI: 1.54-7.51). Conclusion: The findings from this study show that problematic alcohol use is prevalent among college students and EI may provide a protective effect against this deleterious behavior. Given the findings observed in this study, university officials should incorporate EI training into the university curriculum, such as in onboarding courses for freshman and transfer students, to target prevention of potentially harmful alcohol consumption and associated negative health impacts.